The Competency Attainment Outcomes of 1,913 Juveniles Found Incompetent to Stand Trial Janet I. (Journal of Applied Juvenile Justice Services, 2019)
Our study examines the outcomes of remediation services provided to 1,913 juveniles who have been determined to be incompetent to stand trial and ordered into remediation services by the court. These services were offered based upon statutory guidelines legislated in 1999, through a statewide, community-based program maintained by the Virginia Department of Behavioral Health and Developmental Services (VA DBHDS). Recipients of these services were eight through 18-years-old and were predominantly African-American (73%), Caucasian (21%), and Hispanic (3%). Our outcome data indicate that 76% of the youth ordered into remediation services were determined by the court to have been remediated, 19% unlikely to attain competency, and 5% had their charges dismissed. Remediation services were offered within the community and received by the majority of the youth within three months at an estimated cost of $5,000 per juvenile. Rates of remediation differed based upon the age and mental status of the youth receiving services with 7% of youth aged eight to 10 years being remediated compared to 44% of those aged 14 to 16 years of age. Youth with a diagnosis of both intellectual disability and mental disorder were the least likely to be remediated with 51% determined to be unlikely to attain competency and an additional 28% having their charges dismissed. These outcomes are similar to those obtained with incompetent adult defendants, often through costly periods of inpatient hospitalization, raising the question of why states would not provide these due process protections to the most vulnerable youth within the juvenile system.